The Importance of Problem Based Learning in Islamic Higher Education - Nur Kholis (FITK UIN Walisongo, 2018)
This article aims to explain the importance of applying the Problem Based Learning (PBL) method in Islamic Religious Colleges (PTKI). this study uses literature review. The results of the study indicate that PBL is a constructive learning method that uses problems as a trigger for the learning process. This method is important for students in Islamic higher education in constructing their own learning experiences and knowledge, to improve critical thinking skills, problem solving, train communication skills, and improve student learning outcomes. AbstrakArtikel ini bertujuan memaparkan tentang pentingnya penerapan metode Problem Based Learning (PBL) di Perguruan Tinggi Keagamaan Islam (PTKI). penelitian ini menggunakan kajian kepustakaan. Hasil penelitian menunjukkan bahwa PBL adalah metode pembelajaran konstruktivistik yang menggunakan masalah sebagai pemicu proses pembelajaran. Metode ini penting untuk mahasiswa di pendidikan tinggi Islam dalam mengkonstruk pengalaman belajar dan pengetahuan sendiri, untuk meningkatkan kemampuan berpikir kritis, pemecahan masalah, melatih keterampilan komunikasi, dan meningkatkan hasil belajar mahasiswa.